THE EFFECT OF GREEN ACCOUNTING AND INTELLECTUAL CAPITAL ON FIRM VALUE WITH BUSINESS STRATEGY AS A MODERATION VARIABLE - Kusmawati, Siska Dila; Anisah, Nur (Jurnal Akuntansi Bisnis, 2025)
Background: The growing emphasis on sustainability and intellectual capital in corporate decision-making has led to increased interest in understanding their impact on firm value. In particular, business strategy may play a crucial role in moderating these relationships.Objective: This study aims to examine the effect of green accounting and intellectual capital on firm value, with business strategy as a moderating variable.Research Methods: The study focuses on 10 coal sector companies and 10 food and beverage sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. Using a purposive sampling approach, 20 companies were selected as research samples. The hypotheses were tested using SPSS software and multiple linear regression models with Moderated Regression Analysis (MRA).Research Results: The findings indicate that green accounting has a significant positive effect on firm value in coal sector companies but an insignificant negative effect in food and beverage sector companies. Intellectual capital has a significant positive effect on firm value in both sectors. Furthermore, business strategy moderates the relationship between green accounting and firm value, showing a significant negative effect in coal sector companies but a positive effect in food and beverage sector companies. Business strategy also strengthens the positive effect of intellectual capital on firm value in both sectors.Authenticity/Novelty of Research: This study provides new insights by incorporating business strategy as a moderating variable in the relationship between green accounting, intellectual capital, and firm value across different industry sectors.